2013
DOI: 10.1007/s12369-013-0190-2
|View full text |Cite
|
Sign up to set email alerts
|

Living with a Vacuum Cleaning Robot

Abstract: Little is known about the usage, adoption process and long-term effects of domestic service robots in people's homes. We investigated the usage, acceptance and process of adoption of a vacuum cleaning robot in nine households by means of a six month ethnographic study. Our major goals were to explore how the robot was used and integrated into daily practices, whether it was adopted in a durable way, and how it impacted its environment. We studied people's perception of the robot and how it evolved over time, k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
93
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(99 citation statements)
references
References 37 publications
6
93
0
Order By: Relevance
“…However, the temporality of UX, i.e., how the quality of the users' experience develops over time [14], is still an area of research to be further explored [2]. As soon a new technology is deployed, acceptance becomes an issue (e.g., [10], [25]), and technology adoption is crucial. Technology adoption represents a process that ends with a user embracing a technology, i.e., accepting it [24].…”
Section: Ux Over Timementioning
confidence: 99%
See 3 more Smart Citations
“…However, the temporality of UX, i.e., how the quality of the users' experience develops over time [14], is still an area of research to be further explored [2]. As soon a new technology is deployed, acceptance becomes an issue (e.g., [10], [25]), and technology adoption is crucial. Technology adoption represents a process that ends with a user embracing a technology, i.e., accepting it [24].…”
Section: Ux Over Timementioning
confidence: 99%
“…Narrative interviews are open-structured qualitative interviews that aim to evoke reports of personal experiences by the participants [10]. The main task of the interviewer is to stimulate these reports by asking narrative trigger questions.…”
Section: Narrative Interviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, despite the greater attention to the hedonic factors, the utilitarian factor of usefulness seems to be a fundamental basis for engaging in long-term use with a social robot. The importance of practical utility is also stressed by Fink et al (2013), who reported that people who did not perceive the robot to be useful stopped using it after some initial trials.…”
Section: Building Upon the Sera Projectmentioning
confidence: 99%